Persistent food insecurity from policy failures in Malawi - Babu, Suresh Chandra; Sanyal, Prabuddha (Cornell University, 2007)
Even in the era of globalization, several countries in Africa continue to face chronic and persistent food insecurity. Malawi is one such country. Following a weather shock in 2001, Malawi suffered severe food crises during 2001/02 and again during 2003/04. The main causes of these crises were both natural and manmade. Although poor rainfall resulted in low agricultural productivity, inefficient government policies exacerbated the crises. The reduction in per capita food availability due to low production led to a dramatic increase in food prices. The rapid increase in prices, combined with low purchasing power of a large section of the Malawian population, adversely affected household food access. The government’s erroneous food price policies added to the crises, thwarting the efficient functioning of food markets and resulting in starvation-related deaths in some districts. Maize is the dominant food crop in Malawi, and its yield is highly sensitive to weather variations. Several programs and policies have attempted to increase the productivity of maize and help consumers gain better access to food. Yet misguided policies and their inconsistent implementation remain a major impediment to achieving food security for all Malawians. This case study illustrates this proposition with two policy examples. The first example shows that although Malawi’s Starter Pack Program—free distribution of hybrid maize seeds and fertilizers in small packs to smallholder farmers—initially improved food security, premature scaling down of the program to a targeted program during the low-rainfall period of 2001/02 resulted in food crisis. The second example shows how government intervention to subsidize maize prices through parastatal outlets kept maize prices artificially low. This action led to poor incentives for private traders to import food during the periods of food deficit and thereby contributed to the food crisis. Several policy responses can address production and market failures and help in avoiding future food crises. These responses include developing small-scale irrigation systems, increasing smallholder access to modern inputs, and improving market infrastructure and trade. Social safety nets to smooth consumption shocks and provide income opportunities during crisis periods are also important. Consistent and well-informed policies can help reduce the impact of future food crises. The challenge to Malawian policy makers is to design, sequence, and implement such policies and programs. Your assignment is to develop a set of policy recommendations that will prevent future food crises in Malawi.